ECOLOGICAL AND ECONOMIC PROBLEMS OF LINEAR PROGRAMMING - Fedorova, Anastasia; Fahretdinova, Victoria (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2016)
The article presents the results of teaching the topic "Substantial models of linear programming" for the 3rd year students from the faculty of physics and mathematics of Pskov State University. Given topic contributes to a better understanding of the content of the problem of linear programming and demonstrates applied mathematics resources. The article analyzes the tasks, causing the greatest difficulty for students studying linear programming, and conclusions are made.